2016
DOI: 10.1007/s10120-016-0652-y
|View full text |Cite
|
Sign up to set email alerts
|

Distinct expression profile of key molecules in crawling-type early gastric carcinoma

Abstract: CRA demonstrated unique clinicopathological characteristics and showed a distinct expression profile of key molecules, which was close to that of a null phenotype. These results support the classification of CRA as a distinct subgroup of gastric adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 16 publications
(42 reference statements)
1
16
0
Order By: Relevance
“…Several studies demonstrated that CRA was associated with specific histological patterns and had characteristic clinicopathological findings [3][4][5][6][7]. Despite its characteristic histological features, CRA is not included in the WHO classification as a distinct histological subtype.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies demonstrated that CRA was associated with specific histological patterns and had characteristic clinicopathological findings [3][4][5][6][7]. Despite its characteristic histological features, CRA is not included in the WHO classification as a distinct histological subtype.…”
Section: Discussionmentioning
confidence: 99%
“…CRA may occur with low frequency in Western countries that have a low prevalence of H. pylori infection, which can produce intestinal metaplasia. Some recent studies indeed suggested that CRA could be considered as a specific histological entity of GC [3,5], but to date CRA has not yet been histologically established as a recognizable subtype. CRA having lowgrade cellular atypia may in fact closely mimic intestinal metaplasia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations